Activation of polyethylene terephthalate using different plasma treatments - Ferreira, A. (2010)
In this work, several types of plasma treatments were performed on the surface of polyethylene terephthalate (PET) substrates, using a custom-made reactive magnetron sputtering equipment. The evaluation of modifications on the surface of the polymer was carried out through Atomic Force Microscopy (AFM), X-ray diffraction (XRD), Fourier Transform Infrared Spectroscopy (FTIR) and contact angles measurements (CA). The base pressure before the plasma treatments was always below 2×10-4 Pa and the working pressure was included between 3×10-2 and 8×10-1 Pa (plasma on), depending on the treatment applied to the samples. Experimental results show that an increase in contact angle is related to an increase in the average roughness. Contact angle values vary from 71 to 84º, with average roughness values ranging between 3.3 and 7.2 nm for different surface treatments. FTIR in mode of attenuated total reflection show that there were no significant chemical changes in the material, while XRD reveals that there are no detectable changes either in the structure of the polymers. The curves of stress - strain are similar to the material without treatment: linear up to about 8 % of strain, followed by a plastic deformation. The Young modulus, yielding stress and strain of the materials stay, within experimental error, within the values obtained for the untreated polymer: 2.1 GPa, 109.4 MPa and 153.3 MPa, respectively. The adhesion of the titanium nitride (TiN) to the polymer is very strong, without any traces of film removal, independent the test method, ASTM - D3359 - 97 or peeling test at 90 °. The set of results shows that the plasma treatments are effective in promoting adhesion of functional thin films, without any degradation of the polymers base properties (chemical, structural or even mechanical ones).